Rance Dehner : Lawman's Duty - Book 7 - Clay, James (Thorndike, Maine : Center Point Large Print, 2025)
"Thad Jarrett became a living legend when he outdrew and killed the vicious gunfighter, Music Matt McCall. Twenty- two years later, McCalls son is presumably hiding out in the town of Travis, Arizona, where Jarrett is now the sheriff. Like his father, the son sings hymns. Unlike his father, the son of Music Matt McCall strikes late at night leaving behind nothing but corpses. Jarrett wonders if the killings arent connected to a vote the town is soon to take on whether to permit a railroad to come into Travis. The lawman calls on a friend, Rance Dehner, for help. Dehner arrives as a gunman is shooting up a rally opposing the railroad. That is only the beginning. Dehner suspects powerful forces are at work as a national magazine arranges for a reenactment of the famous gunfight between Jarrett and McCall. But the current horror of brutal murders and the threat of more killings allows Rance Dehner little time to muse on the past. He must employ his Colt against a large number of hooded outlaws. The violence and bloodshed lead both Jarrett and Dehner to a final terrifying resolution."--
Keywords: Detectives -- Fiction; Gunfighters -- Fiction; Serial murder investigation -- Fiction; Corruption -- Fiction; Railroads -- Fiction; Arizona -- Fiction; Western fiction; Large print books